Gen Z Era Linguistic Impoliteness on Using TikTok Social Media - Dwi N. , Adika; Breliana P. R, Marshanda; Khoiriyah R, Silvi; Erlina T, Arini; Tiara N, Cindy (KIRANA : Social Science Journal, 2025)
Politeness in language is fading, especially among Gen Z. The development of technology and digitalization facilitates the spread of impolite language, especially on social media such as TikTok. This study aims to analyze impolite language on TikTok in the Gen Z era with a focus on: 1) factors causing impoliteness; 2) forms of Gen Z language use that are not in accordance with politeness; and 3) the impact of social media on the development of Gen Z language. The method used is observation, with an analysis of the TikTok comment column from 15 users over the past five months. This study is important for understanding changes in communication behavior among the younger generation and is expected to provide insight into the use of appropriate language and its implications in a social context.